2 m minus 3 upon 5 is equal to M + 4 upon 5
Attachments:
![](https://hi-static.z-dn.net/files/d16/51116e7078348653351cd17a39a0278a.jpg)
Answers
Answered by
3
Answer:
the answer is in the attachment.
Attachments:
![](https://hi-static.z-dn.net/files/d8e/5658e31af4b89e0a63f2364da32b3828.jpg)
Answered by
2
Answer:
2m-3/5 = m+4/5
2m-m = 4/5+3/5
m = (4+3)/5
m = 7/5
I hope it helps you!!!
Similar questions
History,
6 months ago
Math,
6 months ago
English,
6 months ago
Biology,
1 year ago
Social Sciences,
1 year ago